2014
DOI: 10.1515/sg-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of SSR, ISSR and AFLP markers for characterization of selected genotypes of Himalayan Chir pine (Pinus roxburghii Sarg.) based on resin yield

Abstract: A set of 19 SSR (Simple Sequence Repeats), 9 ISSR (Inter-Simple Sequence Repeats) and 5 AFLP (Amplified Fragment Length Polymorphism) primer combinations were used to evaluate the variability among 53 genotypes of Pinus roxburghii selected based on resin yield from the natural zone of occurrence of this species in Uttarakhand, India. The selected trees of pine varied in resin yield from 0.25 to 8 kg/year/tree. Based on the comparative assessment of SSR, ISSR and AFLP markers, SSR markers were found most polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
(20 reference statements)
3
4
1
1
Order By: Relevance
“…Many researchers have used SSR and ISSR markers to detect the genetic diversity in sugar beet (Izzatullayeva et al, 2014, Abbasi et al, 2015, Taški-Ajduković et al, 2017and Bogacheva et al, 2019. As expected, the ISSR marker showed higher both of average and the total number of alleles, which is in agreement with the results of Rawat et al (2014) and Abdollahi-Mandoulakani et al (2015). In contrast, the SSR marker detected a higher polymorphism percentage than the ISSR marker.…”
Section: Polymorphism and Variability Evaluationsupporting
confidence: 66%
“…Many researchers have used SSR and ISSR markers to detect the genetic diversity in sugar beet (Izzatullayeva et al, 2014, Abbasi et al, 2015, Taški-Ajduković et al, 2017and Bogacheva et al, 2019. As expected, the ISSR marker showed higher both of average and the total number of alleles, which is in agreement with the results of Rawat et al (2014) and Abdollahi-Mandoulakani et al (2015). In contrast, the SSR marker detected a higher polymorphism percentage than the ISSR marker.…”
Section: Polymorphism and Variability Evaluationsupporting
confidence: 66%
“…erythropappus and E. incanus populations were characterized by low cpDNA variation and overall diversity and no population differentiation. The results for E. erythropappus showed contrasting patterns to those reported in previous studies using nuclear markers, such as isozymes, RAPD and ISSR; these studies showed high population diversity and overall diversity and significant differentiation between populations (Estopa et al 2006;Moura 2005;Pádua et al 2016) probably due the higher mutation rate of those markers than cpDNA (Provan et al 1999;Rawat et al 2014). Unlike the cytoplasmic genome, the chloroplast genome is clonal, or inherited maternally, and historical events, such as glaciation and climatic change, have a greater impact on its variation over geological time (Avise 1994;Avise et al 1987).…”
Section: Genetic Analysescontrasting
confidence: 63%
“…The values of Rp were relatively high for SCM101 and SCM109. In the work of Rawat et al ( 2014 ), the values of Rp calculated for SSR markers were lower than for ISSR and AFLP. The authors related it to the lower number of detected bands in comparison with other tested marker systems.…”
Section: Discussionmentioning
confidence: 78%